Porous Graphene Oxide/Porous Organic Polymer Hybrid Nanosheets Functionalized Mixed Matrix Membrane for Efficient CO2 Capture - He, R.; Cong, S.; Wang, J.; Liu, Jian; Zhang, Y. (American Chemical Society, 2019)
The computational simulation of porous graphene oxide (PGO) indicated that it has great potential for the preparation of gas separation membranes. However, scaling up the manufacture of multilayer, defect-free porous graphene oxide membrane with consistently sized nanopores is extremely challenging. Here, we prepared layer-by-layer CO2-philic Pebax@1657 membranes that were functionalized by o-hydroxyazo-hierarchical porous organic polymers (o-POPs) and PGO. The d-spacing of pristine PGO could be finely regulated through CO2-philic o-POPs to facilitate the permeability of CO2. In addition, the o-POPs exhibit “N2-phobic, CO2-philic” properties with the phenolic hydroxyl and the azo group. The best of the POP-PGO membrane exhibits that the CO2 permeability and ideal selectivity of CO2/N2 are 232.7 Barrer and 80.7, respectively, and it has surpassed the Robeson’s upper bound (2008).